Algorithms with new parameter conditions for split variational inclusion problems in Hilbert spaces with application to split feasibility problem. (2nd April 2016) - Chuang, Chih-Sheng
Abstract : Split variational inclusion problem is an important problem, and it is a generalization of the split feasibility problem. In this paper, we present feasible algorithms for the split variational inclusion problems in Hilbert spaces, and provide convergence theorems for these algorithms. As application, we study the split feasibility problem in real Hilbert spaces. Final, numerical results are given for our main results.